USEFUL PLANTS IN THE TRADITIONAL AGROFORESTRY SYSTEMS FROM THE ECUADORIAN COAST - García Cruzatty, Luz (2008)
The study was carried out in the Middle Basin of the Río Guayas, Ecuador, in the area corresponding to the cantons Mocache and Palenque. The inventory of the species was realized by participative journeys. The species were classified according to the Cronquist Filogenetics System. The data about the use of the species were obtained by chats and non formal interviews. It was determined that the farmers from the Middle Basin of the Río Guayas know and they use 262 vegetable species that belong to 67 families and 164 genuses. The most common vegetable families were: Anacardiaceae, Papilonaceae, Solanaceae, Rutaceae, Musaceae and Lamiaceae, with more than ten species each one. Some 21 types of uses were documented, of which the most important are: nutritious, medicinal and construction, which demonstrates the concern of the families to satisfy their basic necessities. Most of the used species are trees, followed by grasses and bushes. Among the species of major importance for the multiple uses and products that are obtained are: Persea americana Mill. (aguacate), Artocarpus altilis Fosberg (fruta de pan), Musa sp. (plátano), Manguifera sp. (mango), Phythelephas aequatoriales Spruce (cade), Inga edulis Matius (guaba de bejuco), between others.